Natural Enrichment of Trace Elements in Surface Horizons of Calcareous Soils (La Mancha, Spain) - Sandra Bravo Martín-Consuegra; Jose A. Amorós Ortíz-Villajos; Caridad Pérez-de-los-Reyes; Francisco J. García Navarro; Rolando Ruedas Luna; Raimundo Jiménez Ballesta (Journal of Chemistry)
The study of five soil profiles developed on carbonatic sediments of Tertiary Miocene origin has been carried out. The topography of the area was basically flat and the traditional uses of the soils are the cultivation of dry cereals and grapevine. The geochemical characterization of the aforementioned profiles involves a study of the contents of major and trace elements among other pedologic aspects (texture, pH, organic matter, etc.). The results of this study also indicate a superficial enrichment of trace elements due to the leaching of Ca and moderate biological and anthropic activity. We can consider strontium, Sr, as the trace element that characterizes these limy soils (435 mg/kg average content in total soil and 708 mg/kg in the original rock). These contents are similar to the average value in Castilla-La Mancha of 380 mg/kg and are higher than the average in world soils of about 200 mg/kg. High levels of dangerous or pollutant elements (Cd, Hg, Pb, Cu, Zn, or Ni) were not detected. The majority of trace element anomalies are related to calcareous material and the leaching of calcium carbonate (Ca), while the influence of the anthropogenic factor is secondary. Soil quality does not indicate toxicity although surficial enrichment suggests a weak threat from consuming crops.